Trauma, Policy and Teaching English Language Learners - Scarff, Bria; Millar, Nathan; Kostouros, Patricia; Crossman, Katie; Abboud, Rida (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2023)
The authors present findings that emphasize a need for trauma-informed policy to mitigate vicarious trauma transmission for teachers who work in English language learning (ELL) classrooms. Qualitative data was collected from 10 stakeholders in Canada using an interpretive-phenomenological methodology. Findings assisted to better understand the impact of institutional policy, or lack thereof, on trauma-informed practices within English language teacher work. Themes that emerged were settlement factors, roles, and responsibilities (personal and professional), and organizational policies. A scan of publicly available information on trauma-informed policy suggested a gap for English language teachers. Current literature on vicarious trauma stresses that trauma-informed practice necessitates an individual and systemic approach to mitigating its effects. A basic scan of potential trauma-informed frameworks was discussed as potential institutional approaches to reduce the impact of vicarious trauma on teachers.